GAMBARAN KUALITAS FISIK AIR DAN PERILAKU PADA PENDERITA PENYAKIT SCABIES DI WILAYAH KERJA UPTD PUSKESMAS PURWANEGARA 1 TAHUN 2023 - Bayu Suseno; Aulia Nur Rahma (Jurnal Ilmiah Medsains, 2024)
Scabies is an environmentally based disease (EBD). Scabies is a parasitic infection caused by the Sarcoptes Scabiei variant hominis mite. Based on the results of the researcher's observations during the community health center work practice, Scabies is one of the diseases that is quite high in the Purwanegara 1 community health center. The purpose of this study was to determine the characteristics, physical quality of water and the behavior of sufferers in the work area of Purwanegara 1  community  health center  in the period  January 2022- January 2023. This study included descriptive research with a cross sectional approach. The population in this study were patients with Scabies in the Purwanegara 1 public health center area who had examined themselves and had conducted counseling with sanitarians in the period January 2022-January 2023. Research sampling using the total sampling method. The data used were primary data from observations and interviews, and secondary data obtained from the Purwanegara 1 public health center. The results of this study found that most Scabies sufferers were aged 17-25 years (19.3%) with male gender (58.1%), educated with elementary level (32.3%), The  physical  quality  of  water  owned  by sufferers is partially unqualified (67.7%) but  respondents have good behavior (90.3%). The description of the physical quality of the respondent's water most of the respondents did not meet the requirements but people with Scabies had good behavior. The suggestion in this study is that people can implement a clean and healthy lifestyle.